Religious freedom in East Asia: historical norms and the limits of advocacy - DuBois, Thomas David (Journal of religious and political practice, 2018)
The introduction of the Western idea of religion to East Asia during the nineteenth and twentieth centuries initiated a transformation so profound that it required the creation of an entire new vocabulary, including a new word for 'religion' itself. However, the fact that new regimes in China and Japan adopted Western terminology does not mean that they uncritically accepted its ideas and assumptions. East Asia was already home to millennia-old traditions of statecraft that subjected religious institutions to the sovereign, and made the moral indivisible from the political. Even as new regimes wrote the language of religious freedom into constitutions and legal codes, they continued to interpret the scope and limits of freedom very differently than they had been imagined by the Christian West or later by Soviet-inspired Marxists. An appreciation of the very different ways that East Asian societies have historically interpreted and adapted the ideas of religious rights and freedoms is vital for understanding why countries like China can speak with apparent sincerity about religious freedom, yet continue to vex the expectations of the international human rights community.